STRATEGI KOMUNIKASI PARISADA HINDU DHARMA INDONESIA ( PHDI) DALAM PEMBINAAN UMAT HINDU DI KOTA KENDARI TAHUN 2020-2021 - Widi Astuti; Ni Made Yuliani; I Nyoman Sueca (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Provides guidance to Hindus is Parisada Hindu Dharma Indonesia, Kendari City. Parisada Hindu Dharma Indonesia or commonly abbreviated as PHDI is the highest assembly of Hindu religious institutions, which was established to serve Hindus in increasing Sraddha and Bhakti based on the Vedic Scriptures, as well as managing and developing Hindus in enhancing their awareness of religious life. Based on this background, researchers are interested in researching the